2014
DOI: 10.7897/2230-8407.050469
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization and Pharmacological Screening of Some Novel Benzimidazole Derivatives

Abstract: The reaction of o-phenylenediamine with anthranillic acid yield compound 2-(1H benzo[d]imidazol-2-yl) aniline (1). The compound (1) was condensed with Chloroacetyl chlorides in the presence of dry benzene to get compound 2-chloro-N-[2-(2,3-dihydro-1Hbenzimidazol-2-yl)phenyl]acetamide.Further it to then treated with KSCN to getan intermediate compound then reacted with corresponding aromatic aldehyde yield compound 5 benzylidene-3-[2-(2,3-dihydro-1Hbenzimidazol-2-yl)phenyl]-2-imino-1,3-thiazolidin-4-one. The co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 28 publications
(24 reference statements)
0
3
0
Order By: Relevance
“…[32]- [34] Some of these compounds are used to fight parasitic diseases such as helminthiases. This is the case for Flubendazole, Mebendazole, Albendazole and Thiabendazole.…”
Section: Anthelminthic Properties Of Benzimidazole Derivativesmentioning
confidence: 99%
“…[32]- [34] Some of these compounds are used to fight parasitic diseases such as helminthiases. This is the case for Flubendazole, Mebendazole, Albendazole and Thiabendazole.…”
Section: Anthelminthic Properties Of Benzimidazole Derivativesmentioning
confidence: 99%
“…The benzenoid and quinoid characteristic C=C stretching vibrations are now observed at 1506 and 1570 cm -1 , respectively, and the typical C-N stretching vibration of the polyaniline backbone now appears at 1302 cm -1 . The peak at 1670 cm -1 corresponds to the characteristic C=N stretching vibration of benzimidazole [21], and the peaks at 1459 and 1220 cm -1 are due to the C=C [22] and C-N [23] stretching vibrations, respectively, of benzimidazole. Altogether, these findings prove the presence of the benzimidazole entity as the side chain in the synthesized polymer.…”
Section: Scheme 1 Illustration Of the Interfacial Polymerization Reac...mentioning
confidence: 99%
“…The results of preliminary biological tests showed that all compounds exhibited significant anthelmintic activity. 5 Vilasrao et al described the synthesis of a library of 2-substituted benzimidazoles and the evaluation of their anthelmintic activity against the adult earthworm E. fetida . Among them, compounds 23–25 exhibited excellent anthelmintic activities which are comparable to that of standard albendazole ( Fig.…”
Section: Introductionmentioning
confidence: 99%